MELIRIK TAKHRIJ SANAD DAN MATAN: HADITS TENTANG ‘ADAA (MENGANIAYA) DALAM MUSNAD AHMAD - Bakir, Mohammad (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2020)
This study explains the important things that is highlighted regarding the takhrij sanad and the honor of the hadith about ‘adaa (persecuting) which only exists in Musnad Ahmad bin Hanbal. The basis of this interest are: first, Ahmad bin Hanbal is known as a person who is loose or tolerant in evaluating the hadith; second, Ahmad bi Hanbal is very close to the period of friends; thirdly, Ahmad bin Hanbal is a great scholar whose scholarship is very doubtful, moreover he is a teacher of Imam Bukhari and Imam Muslim. This study uses a library (library research) approach by collecting data examining the work of Ahmad bin Muhammad bin Hanbal in the book Musnad, Syarahahu wa Shama'a Faharisahu Ahmad Muhammad Syakir, Juz 12 Hadith from number 14,795-16,356 and Software Lidwa Pusaka. The research data uses interactive data analysis with stages including data reduction, data exposure, and conclusion drawing and verification (conclusion drawing / verifying). The result is that in takhrijj the hadith through sanad and matan relating to ‘adaa (persecuting) is to have degrees of hasan (for hadith number 15,425) and saheeh (for hadith number 15,426). Basically the Musnad Ahmad is the largest collection of books that almost contains the book Al-Sittah.Keywords: Takhrij al-Hadits, ‘Adaa, Musnad Ahmad